Optimal setting of DOC relay in distribution system in presence of D-FACTS - Lazhar Bougouff; Abdelaziz Chaghi (Bulletin of Electrical Engineering and Informatics, 2021)
The process of selecting optimal settings for directional over-current relays (DOC relays) is a selection of time dial setting (TDS) and IP (backup current), So that changes in the system of electrical power distribution. In this work, a breeder genetic algorithm (BGA) has been applied to optimal settings of DOC relays with multisystem D-FACTS devices. The simulation consists of two network operation scenarios, scenario without D-FACTS which consisting of coordination of DOC relays against three phase faults, and the second scenarios with multi TCSC. In general, had been verified on optimal settings of relays that the impacts of TCSC insertion in 33-bus distribution system on DOC relays.